As representações sociais da morte e do processo de morrer para profissionais que trabalham em unidade de terapia intensiva uti - Guerra, Débora Rodrigues (2005)
This study aimed to seize the general social representations of doctors and nurses who work in ICUs on the process of death and dying. We also aimed to know the social representations of these professionals in relation to death and the process of dying of people who are under their care, identify factors that influence the construction of these representations and identify similarities and differences between the two professions. The study was conducted from the perspective of the Theory of Social Representations of Serge Moscovici and the Central Nucleus of Jean-Claude Abric. The study was conducted in the Intensive Care Unit of Natal Hospital Center, a private hospital of the city of Natal - Rio Grande do Norte. This is descriptive and exploratory research. Twenty-four (24) professionals were interviewed, twelve (12) nurses and twelve (12) doctors. Data were collected through two instruments: Test of Free Association of Words, semi-structured interview. Later, they were coded, categorized and analyzed according to Content Analysis of Bardin (1977). The words evoked after the use of inducing words - death and dying - and the interviews, led to three thematic categories: Death and dying as a biological event, death and dying as a psychosocial event, death and dying as a transcendental event. As final considerations, we believe that the social representations of the group are translated in death and dying as biological and psychosocial events and anchored in the transcendental aspects, we do not see obvious differences in the testimonies of doctors and nurses , and the factors that interfere the construction of these offices is the culture, including religion